ANALISI KORELASI ASPEK KOGNITIF DAN EKONOMI TERHADAP STATUS GIZI BALITA - Sarimin, Dorce Sisfiani; Tasripin, Mellysa Wulandari; Anwar, Seniwaty; Situmeang, Lamria (Ensiklopedia of Journal, 2025)
Abstract: The nutritional status of children under five is influenced by various interrelated factors, both direct and indirect. Direct causative factors that affect the nutritional status of children under five include an unbalanced diet and infectious diseases. Indirect causative factors can be in the form of maternal knowledge, maternal attitudes and maternal education and family income. The purpose of the study was to analyze the correlation of cognitive and economic aspects of the nutritional status of toddlers. The research design used in this study was cross sectional. The research was conducted in the Lubuk Buaya Health Center work area in September 2024. The study population was toddlers (12-59 months) in the Lubuk Buaya Health Center work area which amounted to 254 toddlers. The sample amounted to 80 respondents. The sampling technique used Simple Random Sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed a relationship between maternal knowledge (p value: 0.015) and family income (p value: 0.020) on the nutritional status of toddlers. It is suggested to the Puskesmas to further improve information sources for mothers of toddlers about the incidence of nutritional status in children and causative factors by conducting regular health counseling and by distributing leaflets or sticking posters.Keywords: Toddlers, Maternal Knowledge, Income.